Vaccine-induced donor-specific HLA antibodies: a case report highlighting sensitization risks in renal transplant waitlisted patients - Kakodkar, Pramath; Shekari, Nooshin; Mainra, Rahul; Webster, Destinie; Pearce, Twyla; Wu, Fang; Mostafa, Ahmed (Frontiers in Immunology, 2025)
BackgroundIn renal transplant waitlisted patients, vaccinations remain the standard of care for infection prevention. The vaccine and its adjuvant sensitizer can be potential sources for the induction of donor-specific antibodies (DSA) against human leukocyte antigens (HLA). These novel HLA antibodies can result in a positive flow cell crossmatch (FCXM), which can make a previously compatible live donor incompatible.Case reportWe present an adult renal transplant waitlisted patient who has had multiple negative T-cell and B-cell FCXM with no detection of DSA at baseline. The patient then received a single dose of pneumococcal conjugate (PCV13) and a second dose of recombinant zoster vaccine (RZV). After these vaccinations, the patient’s FCXM was positive for both T-cells and B-cells and the HLA class I antibodies (A1, 23, 24, 80; B44, 45, 76) showed a calculated panel reactive antibody (cPRA) of 51%. A1 and B44 DSA were detected which predicted incompatibility with the patient’s planned live donor renal transplant. The patient had to enter the kidney-paired donation program instead and receive their transplantation after 16 months.ConclusionRZV or PCV13 vaccines or their adjuvant components can potentially cause allosensitization in renal transplant waitlisted patients. The detection of DSA can result in reduced access to compatible transplants. With advances in HLA immunogenetics, better tools can monitor HLA-specific memory B-cells to provide crucial insights into the primary mechanism of action of HLA DSA antibody formation and suggest interventions to mitigate this memory B-cell activation.